ANALISIS HUKUM PENGELOLAAN HOTEL BERBASIS SYARIAH KHUSUSNYA ASPEK PERLINDUNGAN KONSUMEN DITINJAU DARI PERSPEKTIF HUKUM BISNIS - Ahmad Taufik; Ujang Bahar (Magister Hukum Sekolah Pascasarjana Unida, 2019)
Syari'ah based hotel. Hotel Syari'ah is a concept of a combination of conventional hotel business by incorporating several principles (rules / values) of Islam in it. This concept is one thing that is fairly new, but is in great demand by people who are predominantly Muslim like Indonesia. The approach used in this study is a normative juridical method, namely an approach that uses the concept of positivist legislation which states that law is identical to written norms made and promulgated by authorized institutions or officials. The subjects in this study were the Application of Syari'ah Principles with data sources for hotel general managers, supervisors, and employees. Constraints found in the study include the negative perception of the hotel business that has been built up so far in the community such as that hotels are used for immorality, but after many Syari’ah-based hotels, the community began to shift its paradigm towards hotels, especially syari’ah-based hotels.